1981
DOI: 10.1002/cber.19811140332
|View full text |Cite
|
Sign up to set email alerts
|

Kernresonanzspektroskopische Untersuchungen an Borverbindungen, XIX. 13 C‐NMR‐Studien an Monoaminoboranen und Borazinen

Abstract: Chemische Verschiebungen δ13C von Aminoboranen R2BNR′2 1 und X2BNR2′ 2 sowie von Borazinen (RBNR′)3 3 und (XBNR′)3 4 (X = F, Cl, Br, I, OR, SR, NR2) könen mit der Wirkung eines γ‐Effektes von R und X auf δ13C(BC) und γ13C(NC) erklärt werden. Es bestehen Analogien zu Alkenen, Imoniumsalzen und Benzolderivaten. ‐ Heteronucleare 13C{1H, 11B} Tripelresonanz‐experimente erlauben die Betrachtung scharfer 13C(BC)‐Resonanzsignale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The 31 P{ 1 H} NMR chemical shifts clearly indicate the formation of the ylides. The 11 B NMR resonances are shifted upfield from δ =56.5 to 48.7 ppm for 2 and from δ =54.7 ppm to 47.6 ppm for 1 , respectively; these values perfectly match those reported in the literature for R 2 B−NH 2 …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The 31 P{ 1 H} NMR chemical shifts clearly indicate the formation of the ylides. The 11 B NMR resonances are shifted upfield from δ =56.5 to 48.7 ppm for 2 and from δ =54.7 ppm to 47.6 ppm for 1 , respectively; these values perfectly match those reported in the literature for R 2 B−NH 2 …”
Section: Resultssupporting
confidence: 88%
“…The 11 BNMR resonances are shiftedu pfield from d = 56.5 to 48.7 ppm for 2 and from d = 54.7 ppm to 47.6 ppm for 1,r espectively;t hesev alues perfectly match those reported in the literature forR 2 BÀNH 2 . [17] It should be notedt hat precedents for such reactivity have been published previously for dialkyl boron compounds. The splitting of NH 3 with the formation of R 2 BÀNH 2 takes place in boron compounds featuring Lewis basic substituents, such as R 2 BÀSEt, or with tBuC(O)OÀBEt 2 .…”
Section: Resultsmentioning
confidence: 88%
“…Both the 1 H and the 13 C spectra recorded at ambient temperatures indicated that the two methyl groups attached to the terminal N atom are nonequivalent, as are the two methyl groups attached to the terminal B atom: Internal rotation about the N1-B2 and N3-B4 bonds is presumably restricted by dative p-bonding. 3,4 A possible alternative structure, 1-c (c for closed) consists of a four-membered ring in which the terminal N atom has formed a dative r-bond to the terminal B atom. Indeed, an X-ray investigation of 2,2,6,6-tetramethylpiperidino[(dibromoboryl)tert-butylamino]bromoborane (3) shows that this compound adopts such a structure in the solid phase, and NMR spectra indicate that the structure is retained in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 4. The mechanism of the intramolecular rearrangement of Me 2 NN(BMe 2 ) 2 (2) that renders the two dimethylboryl groups NMR equivalent.…”
mentioning
confidence: 99%